Effect of an Aggression Management and Violence Prevention (AMVP) Training Programme among Nurses Working in Psychiatric and Emergency Settings (Medico Legal Update, 2019)
Introduction: Aggression is a professional hazard for those who are employed in the psychiatric setting.There is evidence that 52% of the nurses working in the emergency department experience physical or otherviolence from clients. There are not many studies conducted in India regarding the application of aggressionmanagement training in a psychiatric setting. Material and Method: A quantitative method was used forimplementing a participatory training programme. There were 44 trainer group nurses and 138 trainee groupnurses from psychiatric, emergency and intensive care settings. The trainer group nurses were trained by theinvestigator and the trainee group nurses were trained by the trainer group nurses. An interpretive exercisewas developed and validated to assess the competency of the nurses on aggression management and violenceprevention. There were two posttests for the trainer group nurses and there was one posttest for the traineegroup nurses. Results: Among the trainer group nurses, majority (93.2%) of the nurses were non-competentduring the pre-test. But all the nurses (100%) were competent during the post-test one and the post-test two.Among the trainee group nurses, majority (97.1%) of the nurses were non-competent during the pre-testand all the nurses (100%) were competent during the post-test. Majority of the key personnel (82%) opinedthat, their staff perform better aggression management practices after the training programme. Conclusion:An aggression management and violence prevention (AMVP) training programme based on participatoryapproach was found to be more effective to empower the nurses to work in psychiatric and emergencysettings.